Second language acquisition in a study abroad context: findings and research directions - Pinar, Alex (Colombian Applied Linguistics Journal, 2016)
The idea that living or studying in the target language country is essential in order to improve linguistic knowledge and understand its culture is widespread. Since the 1980s, a large amount of research has been conducted in order to describe empirically the linguistic benefits gained from the study abroad context. However, over the last decade researchers have expanded research fields and studied important aspects such as the development of intercultural competence and the influence of extra-linguistic factors during study abroad. The aim of this paper is to present a review and synthesis of the most relevant research projects undertaken during the last decade, highlight the different research lines that have been recently utilized, and comment on their findings. This paper also proposes new research directions that could allow us to understand the deeper complexities of the study abroad learning context.